Edukasi Nutrisi dan Optimalisasi Tumbuh Kembang Balita Pada Masa Pandemi COVID19 di Desa Pekajangan Kabupaten Pekalongan - Fitriyani, Fitriyani; Aisyah, Risqi Dewi (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
nutritional problems have a big cause of child mortality in the world, including in Indonesia. Inadequate nutritional intake for children’s needs is very likely to cause nutritional problems. One of the ways to prevent nutritional problems is providing proper nutrition. Parenting education about detecting growth and development of child and providing nutrition will increase parent’s knowledge for detection of developmental disorders in children. Based on in Kedungwuni District Pekalongan’s data in 2019 there are 34 cases of malnutrition, and its highest case in Kabupaten Pekalongan. The method is detecting growth and development with Stimulation of Early Intervention Detection Growth and Development and providing nutrition education for children. The target is mother of children in Pekajangan village. Team doing cooperate with leaders of health care and midwife. The implementation at May-Agustus 2020. The result is increasing ability of children mother about detecting growth and development and increasing of knowledge about toddler nutrition.